Wooden Churches of Lithuania - Tiziana Campisi; Liucija Berežanskytė (Agathón)
Lithuania has a great variety of wooden architectures, among which the churches emerge for their quality and construction characters, prevailing the use of local materials. The strong link between architecture and the uncontaminated nature of places defines the identity of architectures, so that they sometimes appear almost like a large wooden sculpture, carved in a unique piece. The meticulous knowledge of the buildings has created an atlas of construction techniques, proposing itself as a tool for the conservation and preservation of refined building heritage; the atlas is divided according to themes as wood species, processing methods, construction phases, mutual relationship between the various technical units.